Rac1 Is Required for Matrix Metalloproteinase 13 Production by Chondrocytes in Response to Fibronectin Fragments. Issue 6 (30th May 2013) - Long, David L.; Willey, Jeffrey S.; Loeser, Richard F.
Abstract : Objective: Matrix fragments, including fibronectin (FN) fragments, accumulate during the development of osteoarthritis (OA), stimulating the production of chondrocyte matrix metalloproteinase (MMP). The objective of this study was to determine the role of the small GTPase Rac1 in chondrocyte signaling stimulated by FN fragments, which results in MMP‐13 production. Methods: Normal human cartilage was obtained from tissue donors and OA cartilage from knee arthroplasty specimens. Rac1 activity was modulated with a chemical inhibitor, by knockdown with small interfering RNA (siRNA), or with constitutively active Rac or dominant‐negative Rac adenovirus. Cells were treated with FN fragments, with or without epidermal growth factor (EGF) or transforming growth factor α (TGFα), which are known activators of Rac. Rac1 activity was measured with a colorimetric activity enzyme‐linked immunosorbent assay, a pulldown assay, and immunostaining with a monoclonal antibody against active Rac. Results: Chemical inhibition of Rac1, as well as knockdown by siRNA and expression of dominant‐negative Rac, blocked FN fragment–stimulated MMP‐13 production, while expression of constitutively active Rac increased MMP‐13 production. Inhibition of Rho‐associated kinase had no effect. EGF and TGFα, but not FN fragments, increased Rac1 activity and promoted the increase in MMP‐13 above that achieved by stimulation with FN fragments alone. Active Rac was detected in OA cartilage by immunostaining. Conclusion: Rac1 is required for FN fragment–induced signaling that results in increased MMP‐13 production. EGF receptor ligands, which activate Rac, can promote this effect. The presence of active Rac in OA cartilage and the ability of Rac to stimulate MMP‐13 production suggest that it could play a role in the cartilage matrix destruction seen in OA.